2021
DOI: 10.1021/acs.jpcc.1c01104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Pure 2D Antimony Film on Au(111)

Abstract: The synthesis of antimonene and related 2D Sb films on top of metallic substrates has recently become a very active subject due to the strong spin−orbit coupling and the envisaged topological properties of this novel material. Gold has been used as a standard substrate for other 2D films, but in the case of Sb, no success has yet been reported mainly due to the formation of AuSb 2 surface alloy. In this work, we have used low energy electron diffraction, time-of-flight direct recoil spectroscopy, X-ray photoem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…E. D. Cantero et al deposited antimony samples on a clean Au(111) surface at room temperature. 50 After the sample deposition started, TOF-DRS detected the appearance of Sb recoils, and the intensity of the gold recoil peak continued to decrease. After continuous deposition for 30 min, only the appearance of Sb recoil could be detected on the surface of the deposited sample (Fig.…”
Section: Preparation Of 2d Antimonenementioning
confidence: 99%
“…E. D. Cantero et al deposited antimony samples on a clean Au(111) surface at room temperature. 50 After the sample deposition started, TOF-DRS detected the appearance of Sb recoils, and the intensity of the gold recoil peak continued to decrease. After continuous deposition for 30 min, only the appearance of Sb recoil could be detected on the surface of the deposited sample (Fig.…”
Section: Preparation Of 2d Antimonenementioning
confidence: 99%
“…They have used several experimental and theoretical techniques like TOF-DRS, LEED, STM, XPS, and DFT calculations to study growth and structural properties of antimonene deposited on Au (111) for possible electronic applications. [128] Torres et al have synthesized and optimized the synthesis parameters of antimonene hexagons via colloidal approach. Few-layer antimonene hexagons are synthesized in bulk with lateral dimension of 200-300 nm to 2-3 microns with thickness of few nanometers.…”
Section: Electronic and Optoelectronic Applicationsmentioning
confidence: 99%
“…On surfaces of coinage metals, where the interaction of the deposited atoms with the substrate is high, the formation of the desired honeycomb structure is often hindered, giving place either to surface alloys 15,16 or, in the best case, to monoelemental adlayers with other 2D structures. 17 In the case of Cu(111) as a substrate, stanene was grown at low temperatures (∼150 K) 14 in order to avoid the tendency of Sn atoms to replace Cu atoms in the top surface layer and form a surface alloy. In a previous work, we have investigated the growth of Sn on Cu(001) at low temperature, 18 where we showed that surface alloying is inhibited on this surface at temperatures below 170 K. We observed under these conditions the formation of two ordered phases in the range of coverages lower than 0.65 ML, both presenting open honeycomb-like hexagons and pentagons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On surfaces of coinage metals, where the interaction of the deposited atoms with the substrate is high, the formation of the desired honeycomb structure is often hindered, giving place either to surface alloys , or, in the best case, to monoelemental adlayers with other 2D structures . In the case of Cu(111) as a substrate, stanene was grown at low temperatures (∼150 K) in order to avoid the tendency of Sn atoms to replace Cu atoms in the top surface layer and form a surface alloy.…”
Section: Introductionmentioning
confidence: 99%